2018
DOI: 10.4103/gmit.gmit_3_17
|View full text |Cite
|
Sign up to set email alerts
|

Late retroperitoneal hematoma with abscess formation following laparoscopic staging of endometrial cancer

Abstract: Herein, we report a case of a 63-year-old, nonobese, woman who underwent laparoscopic surgical staging for endometrial cancer with pelvic and para-aortic lymph node dissection. After being discharged, the patient presented to the emergency department with fever and abdominal pain, 1 week after the procedure. Abdominal tenderness, fever, and anemia were the key clinical and laboratory findings. A computed tomography (CT) scan revealed a cystic mass with air bubbles, located in the right iliopsoas region. The fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…As for the differential diagnosis of hematoma from the abscess, we reviewed the English literature in MEDLINE for reports on retroperitoneal hematoma with infection and found several case reports [ 24 26 ]. In all these cases, the patients presented with fever or severe inflammatory findings in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…As for the differential diagnosis of hematoma from the abscess, we reviewed the English literature in MEDLINE for reports on retroperitoneal hematoma with infection and found several case reports [ 24 26 ]. In all these cases, the patients presented with fever or severe inflammatory findings in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one previous case report by Lev-Gur et al that describes a vaginal hysterectomy that resulted in a pararenal hematoma; however, this study was not able to demonstrate the hematoma expanding beyond the vaginal cuff due to limitation by ultrasonography, and their lack of utilization of CT [ 9 ]. Other cases of RP hematomas secondary to gynecologic procedures include abscess formation following the laparoscopic staging of endometrial cancer [ 10 ], and pudendal block for vaginal delivery [ 11 ], both of which required non-invasive treatment with antibiotics. Zorrilla et al reported a case of spontaneous rupture of an ovarian artery pseudoaneurysm that required embolization of the right ovarian artery [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In addition, the residual hematoma is an excellent nidus for bacterial infection. 6 This excess fluid can lead to patients requiring urgent surgical drainage or becoming infected, or it can exacerbate eventual chronic inflammatory complications such as capsular contracture. 7 Although surgeons consistently strive for meticulous intraoperative hemostasis and place drains to minimize the fluid collection, the reported rates of seroma and hematoma following mastectomy with direct-to-implant (DTI) reconstruction remain at 6.7% and 3.4%, respectively.…”
mentioning
confidence: 99%